2022
DOI: 10.3390/children9060910
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Three Different Techniques Considering Quality Skills, Fatigue and Hand Pain during a Prolonged Infant Resuscitation: A Cross-Over Study with Lifeguards

Abstract: The aim of the study was to compare the quality of CPR (Q-CPR), as well as the perceived fatigue and hand pain in a prolonged infant cardiopulmonary resuscitation (CPR) performed by lifeguards using three different techniques. A randomized crossover simulation study was used to compare three infant CPR techniques: the two-finger technique (TF); the two-thumb encircling technique (TTE) and the two-thumb-fist technique (TTF). 58 professional lifeguards performed three tests in pairs during a 20-min period of CPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…The trained rescuers in our research obtained compression quality values of around 50%. Although recent research shows that professional lifeguards can perform compressions with over 80% quality on an infant manikin [ 15 ], Martin et al reported that even trained rescuers have difficulty performing adequate compressions during simulated infant CPR [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The trained rescuers in our research obtained compression quality values of around 50%. Although recent research shows that professional lifeguards can perform compressions with over 80% quality on an infant manikin [ 15 ], Martin et al reported that even trained rescuers have difficulty performing adequate compressions during simulated infant CPR [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quality parameters were evaluated and disaggregated in CC quality, V quality, and CPR quality. Each variable was expressed as a percentage; variable calculations were based on the following formulas published in previous studies [ 6 , 15 ]: CC quality, calculated using the formula: (CC with adequate depth + CC with correct chest recoil + CC with adequate rate) ÷ 3. V quality, calculated using the formula: Number of V with adequate volume ÷ Number of total V × 100.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a number of studies have been published that examine modified compression techniques in infants (<1 year old). However, these studies focus on finger placement in relation to the infant's chest with two rescuers rather than the rescuer's position in relation to the infant with a single rescuer [8][9][10][11]. Furthermore, other studies have compared the feasibility of OTH CPR with bag-mask ventilation versus pocket-mask ventilation in locations such as ambulances and hospitals [12,13].…”
Section: Introductionmentioning
confidence: 99%